Fortalecimiento del patrimonio arqueológico inmerso en los paisajes de bosque seco-tropical del municipio de Aipe/Huila (2021)
The department of Huila proposes to recognise Huila as a Sustainable Tourist Destination by strengthening the offer of cultural products, archaeological heritage and nature. The municipality of Aipe Huila, has a tourist potential for its ecosystem of natural landscapes generated by the hills of the tropical dry forest reserve, where it is immersed in the archaeological heritage descended from the ancestors of the Pijao culture that persists in rocks with petroglyphs carved by the aborigines of the region and cultural traditions represented in the community, which make this area generate opportunities, however, at this time are in poor condition despite the fact that the Municipal Mayor has stipulated as archaeological heritage